(untitled) (Scientific journal of the Fergana State University, 2025)
The article talks about the motive of science in the dramas "Mirzo Ulugbek" by Maqsu Sheikhzadeh and "The Life of Galileo" by Bertold Brecht. In these dramas, ideas about the scientific career are presented as examples and analyzed using poetic methods. The work of Maqsud Shaikhzoda, a famous dramatist who has a worthy place in the Uzbek classical literature of the 20th century, dates back to the period of the Second World War. During the years of the Great Patriotic War, the poet mobilized all his creative energy and warmth of his heart to win over the enemy. Most of Bertold Brecht’s work coincided with the war years, and consisted of rebellion against injustice, protection of truth and, most importantly, the fight against war and fascism. The main idea put forward in the works of the German playwright, who spent almost fifteen years in other countries, is the meaninglessness of wars and the oppression and violence, ignorance, and injustice that befell humanity through this, and the themes remain relevant in his works.